Microsatellite marker development in the crop wild relative Linum bienne using genome skimming. (26th May 2020) - Landoni, Beatrice; Viruel, Juan; Gómez, Rocio; Allaby, Robin G.; Brennan, Adrian C.; Picó, F. Xavier; Pérez‐Barrales, Rocio
Abstract : Premise: Nuclear microsatellite markers were developed for Linum bienne, the sister species of the crop L. usitatissimum, to provide molecular genetic tools for the investigation of L. bienne genetic diversity and structure. Methods and Results: Fifty microsatellite loci were identified in L. bienne by means of genome skimming, and 44 loci successfully amplified. Of these, 16 loci evenly spread across the L. usitatissimum reference nuclear genome were used for genotyping six L. bienne populations. Excluding one monomorphic locus, the number of alleles per locus ranged from two to 12. Four out of six populations harbored private alleles. The levels of expected and observed heterozygosity were 0.076 to 0.667 and 0.000 to 1.000, respectively. All 16 loci successfully cross‐amplified in L. usitatissimum . Conclusions: The 16 microsatellite loci developed here can be used for population genetic studies in L. bienne, and 28 additional loci that successfully amplified are available for further testing.